Numerical Study on the Effect of Blade Angle on the Performance Characteristics of a Centrifugal Pump - Naharazmi, Muhammad Nur Salam Naharazmi; Wan Rosli, Wan Nurhayatul Husna; Md Seri, Suzairin (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The main focus of our research is to analyze how different blade angles affects the performance of a centrifugal pump. By using numerical analysis, we hope to gain deeper understanding of how blade angle variations can affect the pump's efficiency., pressure increases and cavitation. Our objectives revolve around examining the connection between blade angle and pump performance, determining the optimal blade angles to achieve better efficiency, and making valuable contributions to the field of pump design and optimization. The research methodology involves utilizing computational fluid dynamics (CFD) simulations to model and analyze the behavior of a centrifugal pump under different blade angles. This numerical analysis allows for a comprehensive exploration of fluid flow patterns, pressure distribution., and performance parameters. The study will employ established CFD software and systematically vary blade angles while monitoring and recording relevant performance to draw meaningful conclusions about the impact of the blade angles on pump characteristics. In conclusion, the numerical study reveals that blade angle affects the performance characteristics of a centrifugal pump. Optimal blade angles were identified to enhance efficiency and pressure distribution with specific recommendations for blade angle adjustments in pump design.